Open windows for natural airflow and environmental noise reduction. (3rd September 2018) - Mediastika, Christina E.; Kristanto, Luciana; Anggono, Juliana; Suhedi, Fefen; Purwaningsih, Hariyati
ABSTRACT: For buildings in tropical climates, the use of open windows for natural ventilation can not only provide low cost and low energy comfort but also provide thermal delight for occupants. However open windows let in environmental noise. The size and location of windows in walls are key but this study set out to determine whether there are any window forms that can effectively reduce the level of sound ingress into a building. A top-hung window was chosen for this study looking at the dimensions of the window opening and its orientation in relation to the environmental noise source. The top-hung form was selected for its potential to balance the functions of allowing airflow while potentially blocking and reducing noise levels with its window pane angle. The window pane was tested in a laboratory at three opening angles: 0° (closed), 5°, and 10° to let the outdoor air in. The angles were also tested in three different orientations in relation to the noise source position: perpendicular, sideways 60°, and sideways 90°. The test was conducted at 1/3 octave band frequency as specified by ASTM E90-09 to obtain the transmission loss, then ASTM E1332-90 was referred to calculate the outdoor-indoor transmission class (OITC) of the specimens. The study revealed that window orientation and extent of the openings and window pane angle have little effect on noise reduction. The paper concludes with a discussion of how higher levels of natural ventilation can be achieved, particularly in noisy urban areas. The top-hung window, once open, barely blocks environmental noise. However, when the window was closed, the perpendicular orientation offered more noise reduction when compared windows placed sideways to the noise source. The adjustable pane-angle of a top-hung window placed perpendicular to the airflow, and thus the noise source, seemed to have the most potential to balance the functions of allowing airflow when opened and reducing significant noise when closed. Nonetheless, an open window that through its design alone can significantly reduce the ingress of ambient noise into a building is still an issue.